Sense of life purpose is related to grades of high school students via academic identity. Issue 11 (November 2022) - Yukhymenko-Lescroart, Mariya; Sharma, Gitima
Abstract: The aim of this observational study was to examine the extent to which sense of life purpose of high school students was related to their grades directly and indirectly via academic identity. Two hundred and thirty-four high school students completed a survey with measures of sense of life purpose, academic identity, and grades. Results from structural equation modeling showed that the direct relationship between sense of life purpose and grades was non-significant. Yet, sense of life purpose was related to grades indirectly via academic identity. These findings indicated that high school students who have a clear sense of life purpose also have a strong academic identity, which is positively related to their grades. These structural relationships were mostly invariant across gender (male, female), grade level (sophomore, senior), and post-graduation plans (educational, non-educational), but also indicated that purpose played an important role in academic identity of high school students with non-educational goals. Overall, results indicated that life purpose can be salient to grades of high school students. The practical implication of this work is in encouraging school teachers, counselors, and other stakeholders to implement educational approaches, discussions, and interventions that can help students clarify and develop their sense of life purpose. Abstract : Life purpose; Purpose in life; Academic identity; Academic performance; High school.